(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education system in our country is achievement oriented than person oriented. It does not deal with the needs of adolescents who are capable of learning to become empowered and to live successfully in this world. This empowerment is very important in these days as there is rapid globalization and urbanization with the breakdown of joint family system leading to more and more nuclear families and decreasing traditional support systems. Academic and family stress, peer pressure, violence, drug abuse, poor infrastructure and social divide are some of the most important problems which an adolescent has to compete with in this rapidly changing society. An empowered adolescent has the competence to cope with the challenges of life using the available resources in such adverse conditions.The present study was conducted to assess the impact of the life skills education program on young girls in the areas of adjustment with parents, siblings, teachers and peers self-awareness in terms of coping with a variety of demands in life and self-respect. One hundred young girls were selected from CIS Kanya Mahavidyalya ,Pundri, Haryana. Fifty young girls were given Life Skills Education (LSE) programme for a period of two months, while the other fifty young girls were taken as control group and were not exposed to any programme. Results revealed that young girls who were given LSE programme had better adjustment with parents, siblings, teachers and peers better perceived self-awareness and better self-respect than those who were not provided any LSE programme. Results indicated that the program prepares the young girls to be a competent person in a changing and competitive society.